Bio-inspired bistable piezoelectric energy harvester for powering animal telemetry tags: Conceptual design and preliminary experimental validation. (March 2022) - Qian, Feng; Liu, Mingyi; Huang, Jianuo; Zhang, Jiajun; Jung, Hyunjun; Deng, Zhiqun Daniel; Hajj, Muhammad R.; Zuo, Lei
Abstract: This paper presents the conceptual design, preliminary experimental validation, and performance evaluation of a novel bio-inspired bi-stable piezoelectric energy harvester for self-powered animal telemetry tags. The overall conceptual design, which includes a bio-inspired attachment and a bi-stable piezoelectric energy harvester, is introduced firstly with a specific application example of marine fish tracking. The self-powered telemetry tag can be externally deployed on fish (dorsal fin) to monitor fish habitats, population, and underwater environment. Inspired by the Venus flytrap's rapid shape transition, a bi-stable piezoelectric energy harvester is developed to scavenge energy from fish maneuvering and the surrounding fluid flow for a sustainable power supply. The bistability of the harvester is characterized by the measured force-displacement curve and double potential wells. A bluff body is integrated to the free end of the bistable piezoelectric energy harvester to enhance the structure-fluid interaction for the large-amplitude snap-through vibrations and higher voltage output. Controlled laboratory experiments are conducted in a water tank on the bio-inspired bi-stable piezoelectric energy harvester using a servo motor system to simulate fish swing motion at various conditions to evaluate the power generation performance. The preliminary underwater experimental results demonstrated that the proposed bio-inspired bi-stable piezoelectric energy harvester could effectively convert fish swing motions into electricity. The device collected 17.25 mJ of energy over 130 s under a peak-to-peak swing angle of 30 o at 1.5 Hz in the capacitor charging experiments. Graphical abstract: Image 1 Highlights: A conceptual design of a self-powered animal telemetry tag was introduced. A bio-inspired bistable piezoelectric energy harvester was developed, characterized, and tested. Underwater energy harvesting from swing motions was demonstrated and studied. More energy was attained from the large-amplitude snap-through oscillation at a low swing frequency.